Dampak Strata Pendidikan, Kompensasi, Dan Loyalitas Terhadap Kinerja Pada Jasa Pendidikan - Syeila Magfiroh Aruji; Siti Sri Wulandari (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
This study analyzes the effect of educational background, compensation, and loyalty on teacher performance at SMK Ketintang Surabaya. The population used was SMK Ketintang Surabayas’ teachers, totaling 104 teachers, and the sample was obtained using the Slovin formula at the error rate limit of 0.05 to get a total of 83 teachers as respondents—selection of the respondent sample using probability sampling technique with simple random sampling. The method used in this study is an explanatory quantitative model using multiple regression analysis tests. The results of the t-test show that educational background has a positive and significant effect on teacher performance, compensation does not have a positive and significant effect on teacher performance, loyalty has a positive and significant effect on teacher performance, and the results of the F test state that educational background, compensation, and loyalty simultaneously have a positive and significant influence on the performance of teachers of SMK Ketintang Surabaya.